2021
DOI: 10.3390/educsci11110702
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Investigating Mental Wellbeing of University Academics during the COVID-19 Pandemic

Abstract: COVID-19 has impacted Higher Education worldwide. While several studies have examined the effects of the pandemic on students, few have addressed its impact on academic staff. Here, we present both survey (n = 89) and interview (n = 12) data highlighting the pandemic-induced effects on academics from various disciplines and career stages. Data was collected between May and September 2020, aiming to capture and understand the immediate effects of the U.K. lockdown on the academics examining demographic and empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 34 publications
(39 reference statements)
6
44
1
2
Order By: Relevance
“…Another study highlighted a positive, significant correlation between coping strategies and subjective well-being, evidencing the role of coping strategy in reducing anxiety and stress (Achour et al, 2021). Institutional support and academics' overall satisfaction with homeworking during shutdown was consistent among two studies (Dinu et al, 2021;Leal Filho et al, 2021). Findings showed that academics continued to work during shutdown with little loss of momentum, viewed online education positively and were satisfied with home-working infrastructure and institutional support, although the degree varied between continents.…”
Section: Discussionmentioning
confidence: 82%
“…Another study highlighted a positive, significant correlation between coping strategies and subjective well-being, evidencing the role of coping strategy in reducing anxiety and stress (Achour et al, 2021). Institutional support and academics' overall satisfaction with homeworking during shutdown was consistent among two studies (Dinu et al, 2021;Leal Filho et al, 2021). Findings showed that academics continued to work during shutdown with little loss of momentum, viewed online education positively and were satisfied with home-working infrastructure and institutional support, although the degree varied between continents.…”
Section: Discussionmentioning
confidence: 82%
“…However, resources such as social support (e.g., support from colleagues) and online communication options (e.g., attending virtual social gatherings) helped many respondents to meet the social challenges of working from home during the pandemic. The importance of such resources has been highlighted in previous studies (Sjølie et al, 2020;Dinu et al, 2021). These resources are very important because they can create a feeling of togetherness among academics who work from home (Hacker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The personal characteristics described here constitute antecedents for learning and form the basis of the model to be investigated (see Figure 1 ). They may function as a buffer or as an amplifier for the evaluation and emotional responses to environmental-related strain as experienced in the COVID-19 pandemics ( Dinu et al, 2021 ; Godoy et al, 2021 ; Holt-Gosselin et al, 2021 ).…”
Section: Learning and Performance In Adverse Circumstancesmentioning
confidence: 99%
“…Just as the population in general, university students were affected by affective sequelae of the circumstances during the pandemic, such as excessive feelings of stress or anxiety. Exacerbation of anxiety in the wake of the pandemic was related to usage of maladaptive cognition and coping strategies ( Dinu et al, 2021 ; Godoy et al, 2021 ; Holt-Gosselin et al, 2021 ). These hitherto unknown circumstances of learning posed a threat to wellbeing and mental health which subsequently may have also impacted students’ learning and academic achievement ( Andrews and Wilding, 2004 ; Barch et al, 2019 ; Charbonnier et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%